2019
DOI: 10.1080/01694243.2019.1571660
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of hybrid materials based on graphene oxide and silica nanoparticles and their effect on the corrosion protection properties of epoxy resin coatings

Abstract: To cite this article: Aghiles Bouibed & Rachida Doufnoune (2019) Synthesis and characterization of hybrid materials based on graphene oxide and silica nanoparticles and their effect on the corrosion protection properties of epoxy resin coatings,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 67 publications
(81 reference statements)
3
19
0
Order By: Relevance
“…The infrared analysis is another characterization methods that are commonly used in synthesized compounds 68,69 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrared analysis is another characterization methods that are commonly used in synthesized compounds 68,69 .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we followed the standard procedure reported in the literature 68,69 , using a Phillips FTIR model PV-9512 spectrophotometer and KBr tablets.…”
Section: Methodsmentioning
confidence: 99%
“…In the FTIR spectrum of GO, peaks at 1722 and 1618 cm −1 indicate the presence of C═O and C═C functional groups, respectively. Compared with the FTIR spectra of GO-HGMS, the C-O-C absorption peak at 1226 cm −1 disappears, and new absorption peaks appear at 1409, 1069, and 798 cm −1 , which are attributed to C-N, Si-O-C, and N-H absorption, respectively [ 29 ]. In conclusion, in the reaction, the intermediate structure of ─NH 2 obtained by HGMS and KH550 reacted with the ─COOH of the reactant GO to produce a new compound, namely, GO-HGMS.…”
Section: Resultsmentioning
confidence: 99%
“…Their results show that the GO-FAC hybrid filler has a significant effect on improving the tensile and wear resistance of epoxy resin composites; when the content is 0.5 wt%, both properties are optimal. Ramezanzadeh et al [ 28 ], Bouibed et al [ 29 ], and Pourhashem et al [ 30 ] prepared GO-SiO 2 hybrids and filled them into epoxy coating; they reported that the introduction of GO-SiO 2 hybrids into the epoxy coating enhances the corrosion resistance and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] TiO 2 particles as fillers could improve the mechanical performance, corrosion resistance, and tribological properties of pristine epoxy matrix. [ 28 ] However, the dispersion quality of nanofillers in polymer matrix was a key issue in controlling the properties of nanocomposites. Various approaches were attempted to improve the dispersion states and prevent the agglomerations of nanofillers in the epoxy.…”
Section: Introductionmentioning
confidence: 99%